Role of VEGF-A and LRG1 in Abnormal Angiogenesis Associated With Diabetic Nephropathy - Zhang, Afei; Fang, Huawei; Chen, Jie; He, Leyu; Chen, Youwei (Frontiers in Physiology, 2020)
Diabetic nephropathy (DN) is an important public health concern of increasing proportions and the leading cause of end-stage renal disease (ESRD) in diabetic patients. It is one of the most common long-term microvascular complications of diabetes mellitus that characterized by proteinuria and glomerular structural changes. Angiogenesis has long been considered to contribute to the pathogenesis of DN, whereas the molecular mechanisms of which is barely known. Vascular endothelial growth factor A (VEGF-A) plays a major role in mediating angiogenesis and its upregulation is associated with abnormal angiogenesis in DN. Anti-VEGF-A therapies in diabetic animals have shown beneficial effects in preventing DN progress. However, growing evidence indicates it may induce proteinuria and glomerular injury in both basic and clinic experiments. It is therefore essential to understand other angiogenic factors in DN in order to develop more effective therapies. Leucine-rich α-2-glycoprotein 1 (LRG1) is a novel pro-angiogenic factors involved in the development of DN via enhancing ALK1 signaling pathway. Hence, the LRG1 may serve as a novel therapeutic target for DN. This review will focus on discussing the role of VEGF-A and LRG1 in angiogenesis associated with the development of DN, with the aim of evaluating the potential of anti-angiogenesis therapy in patients with DN.